IMPLEMENTING THE COORDINATION FUNCTION OF CONTROLLING OF SPATIAL UTILIZATION IN THE NORTH BANDUNG AREA AS A STRATEGIC AREA OF WEST JAVA PROVINCE (Journal of Namibian Studies : History Politics Culture, 2023)
The North Bandung area (KBU) based on Regional Regulation of West Java Province Number 22 of 2010 is designated as a provincial strategic area because it has a function as a water catchment area which supplies around 60% of the water needs of the people below it, if it is not maintained properly it will potentially cause environmental problems that have a very broad impact on life. However, KBU has extraordinary attractiveness that can provide economic benefits for many investors, so massive commercial development in this area is unavoidable. KBU is administratively located in 4 (four) districts/cities, namely Bandung Regency, West Bandung Regency, Bandung City and Cimahi City. Therefore, controlling development in this area requires good coordination between the provincial government as the representative of the central government and the four district/city regional governments. In reality, coordination did not run optimally, coordination carried out by the Province only with the district/city government based on the location of the land requested, without considering the granting of development permits in one area could have an impact on other districts/cities. For district/city governments, there is no vertical coordination regarding the granting of building permits at the KBU, because the district/city governments only implement the governor's recommendations in issuing these permits. Thus, when the investor has pocketed the governor's recommendation, the district/city government will follow up on the licensing process. On the other hand, the Provincial Government thinks that the governor's recommendation is not a ticket to obtain a permit, but as a consideration for the district/city government when they want to issue a land use permit or construct a building in a KBU. The different perceptions between the Provincial and Regency/City Governments show that coordination in the issuance of permits at the KBU has not been perfect, which in fact provides benefits for investors, even though it has the potential to harm the surrounding community if the increasingly rampant development at the KBU does not take into account environmental damage.